2018
DOI: 10.1093/cercor/bhy179
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Nicotine Exposure Induces Dysregulation of Mesocorticolimbic Activity States and Depressive and Anxiety-like Prefrontal Cortical Molecular Phenotypes Persisting into Adulthood

Abstract: Considerable evidence demonstrates strong comorbidity between nicotine dependence and mood and anxiety disorders. Nevertheless, the neurobiological mechanisms linking adolescent nicotine exposure to mood and anxiety disorders are not known. Disturbances in the mesocorticolimbic dopamine (DA) system, comprising the prefrontal cortex (PFC), ventral tegmental area (VTA), and nucleus accumbens (NAc), are correlates of mood and anxiety-related symptoms and this circuitry is strongly influenced by acute or chronic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 67 publications
5
57
0
Order By: Relevance
“…Our findings suggest that adolescent cannabinoid exposure most likely alters the function of the mesolimbic pathway, as differences were found primarily on the ascending limb of the dose response function. In support of this notion, adolescent cannabinoid or nicotine exposure has previously been shown to alter monoaminergic signaling [37][38][39][40] . However, in our study, nicotine alone was ineffective in altering later drug taking behaviors in males, either in combination with the cannabinoid or alone.…”
Section: Impact Of Adolescent Drug Exposure On Adult Nicotine Intakementioning
confidence: 87%
“…Our findings suggest that adolescent cannabinoid exposure most likely alters the function of the mesolimbic pathway, as differences were found primarily on the ascending limb of the dose response function. In support of this notion, adolescent cannabinoid or nicotine exposure has previously been shown to alter monoaminergic signaling [37][38][39][40] . However, in our study, nicotine alone was ineffective in altering later drug taking behaviors in males, either in combination with the cannabinoid or alone.…”
Section: Impact Of Adolescent Drug Exposure On Adult Nicotine Intakementioning
confidence: 87%
“…In a recent study, Jobson and colleagues used a rodent model of adolescent neurodevelopment to show that exposure to nicotine during a critical period of adolescent neurodevelopment led to long-term behavioural, neuronal and molecular phenotypes consistent with mood and anxiety-related disorders, including an alteration in neuronal activity states in both dopaminergic neuronal populations in the mesolimbic VTA, and increased spontaneous neural activity in the PFC. 28 This suggests a convergence of nicotine-induced neuroadaptation in the mesocorticolimbic system, leading to neuropsychiatric phenotypes which persist into adulthood, and has implications for the development of pharmacological interventions to prevent or reverse the long-term effects of nicotine exposure, as well as in identifying those who may be at increased risk from nicotine exposure during select periods of neurodevelopment.…”
Section: Effects Of Nicotine On the Brainmentioning
confidence: 99%
“…In the cross-sectional Nord-Trøndelag Health Study (HUNT-2), conducted with 60,814 participants, a significant association was found between smoking and MADD (OR=1.82; 95%CI: 1.69–1.95) 33. Some authors investigated the effect of nicotine on the central nervous system 34. In animal models, exposure to nicotine in adolescence was associated with anxiety- and depression-like behaviors due to the persistent state of hyperactive dopamine activity in the ventral tegmental area concomitant with hyperactive neuronal activity states in the prefrontal cortex 34.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors investigated the effect of nicotine on the central nervous system 34. In animal models, exposure to nicotine in adolescence was associated with anxiety- and depression-like behaviors due to the persistent state of hyperactive dopamine activity in the ventral tegmental area concomitant with hyperactive neuronal activity states in the prefrontal cortex 34. In addition, smoking could be associated with MADD because this behavior is not very socially acceptable in Brazil, negatively affecting women’s self-esteem, as has already been reported in a different cultural setting 32…”
Section: Discussionmentioning
confidence: 99%